Dormência física em sementes: compreendendo o ciclo de sensibilidade e os complexos water gap - Ailton Gonçalves Rodrigues Junior (2018)
Physical dormancy (PY), characterized by the presence of a water-impermeable layer in the fruit/seed coat, is one of the most recurrent kind of dormancy in seeds. However, an ample investigation about PY is still needed to understand better this complex mechanism. A two-stage model has been described to break PY in seeds, wherein the first step can be reversible between two stages (‘insensitive’ ↔ ‘sensitive’), becoming permeable in the second step. This feature makes physically dormant seeds to present sensitivity cycling, which regulates the timing of germination, which has been reported for herbaceous species from temperate zones only. Another important aspect about PY is that the seed size controls the dormancy, but how this affects the dormancy is still unknown. Seed structures like hilum, micropyle and lens, act as water gaps, in which the lens is the most common kind of water gap. The pleurogram, a seed structure which function is still unknown, has several fissures which signalize for a possible role in water uptake. Senna, a highly diverse and widespread genus which seeds have PY only, was selected to test our hypothesis in relation to sensitivity cycling, the effect of seed size on dormancy, the function and evolution of the pleurogram and other structures on PY. To test our hypothesis, it was addressed the following questions: (1) Can species from tropical zones and tree habit have sensitivity cycling? (2) If the seed size mediates breaking PY, how does this mechanism work? (3) What is the function of pleurogram in seeds with PY? It was confirmed in this study that sensitivity cycling is not a trait of herbaceous species from temperate zones only. This also occurred for the tropical tree species Senna multijuga. In this species, seed size mediates dormancy break, which is regulated by the water content and the ratio between palisade layer thickness and seed mass. Further, the pleurogram was described as a water gap for some physically dormant seeds. Preliminary results indicate the ancestral character related to the functionality of the pleurogram, structure present in primitive Senna species. Also, the lens may be a most recent structure during the evolution of PY.